Dimensional compatibility of rigid ventilating bronchoscopes with pediatric airway anatomy using different recommendations for age‐related sizing—A bench study. Issue 11 (25th August 2021) - Kemper, Melanie; Kemper, Michael; Nicolai, Thomas; Dave, Mital H.; Henze, Georg; Weiss, Markus
Abstract: Background: Appropriate size selection of pediatric rigid bronchoscopes is fundamental to avoidance of airway trauma and to a high success rate with the first intubation attempt. The aim of the present study was to compare the outer diameters of pediatric rigid bronchoscopes with the anatomical data on the pediatric airway. Methods: Outer diameters (OD) of pediatric rigid ventilating bronchoscopes as given by the manufacturer were compared with published computed tomography internal diameters (ID) of the cricoid outlet, the trachea as well as the left and right proximal mainstem bronchus, using six published recommendations for age‐related size selection. The ratios between a specific OD and ID were calculated and given as percentage values (%) for lower and upper age ranges. Results: Nominal sized 2.5, 3, 3.5, 3.7, 4, 4.5, 5, and 6 rigid bronchoscopes were included. In five recommendations, the rigid bronchoscopes' OD was larger than the internal cricoid diameter in the upper age range, whereas in one recommendation the ratio (OD rigid bronchoscope to ID of cricoid) ranged between 77% and 90% for the upper age and between 95% and 109% for the lower age range. In only one of the six recommendations was the rigid bronchoscope OD larger than the tracheal ID. Ratios for the left and right proximal mainstem bronchus ranged from 70% to 146% for the upper and from 78% to 156% for the lower age range, with the highest ratios for the left proximal mainstem bronchus. Conclusion: Based on this in vitro study, most of the recommendations analyzed result in a balanced fit of rigid bronchoscopes within the cricoid. Since the left mainstem bronchus is considerably smaller than the cricoid, any insertion on this level will require careful endoscopic guidance to avoid damage to the left mainstem bronchus.